2004
DOI: 10.1093/cercor/bhh023
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Rapid Spatial Orienting Towards Fearful Faces

Abstract: We investigated the spatio-temporal dynamic of attentional bias towards fearful faces. Twelve participants performed a covert spatial orienting task while recording visual event-related brain potentials (VEPs). Each trial consisted of a pair of faces (one emotional and one neutral) briefly presented in the upper visual field, followed by a unilateral bar presented at the location of one of the faces. Participants had to judge the orientation of the bar. Comparing VEPs to bars shown at the location of an emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

71
544
13
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(632 citation statements)
references
References 86 publications
(133 reference statements)
71
544
13
4
Order By: Relevance
“…Focusing on late positive potentials, the present findings demonstrate that emotionally arousing pictures affect the processing of subsequently presented pictures, irrespective of whether these pictures depicted emotional or neutral contents. These findings are consistent with the notion of interference and competition for processing resources suggested by cognitive and neuroscientific studies [23,[32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…Focusing on late positive potentials, the present findings demonstrate that emotionally arousing pictures affect the processing of subsequently presented pictures, irrespective of whether these pictures depicted emotional or neutral contents. These findings are consistent with the notion of interference and competition for processing resources suggested by cognitive and neuroscientific studies [23,[32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…More generally, this finding is congruent with our main hypothesis that reward-associated stimuli orient attentional resources because of their affective relevance. Indeed, experiments testing positive and negative emotional stimuli found similar effects as our experiments by showing an attentional orienting appearing after 100 ms (e.g., Brosch et al, 2008;Pourtois, Grandjean, Sander, & Vuilleumier, 2004). Note however that in our attentional paradigm, stimuli used as cues were very briefly exposed, but they were not masked.…”
Section: Discussionsupporting
confidence: 81%
“…It is therefore possible that like the findings of Holmes, et al (2008), high-anxious individuals in the current study showed an enhanced P1 and a reduced N1, a pattern similar to the P1 and EPN findings in the Holmes, et al study. The enhanced P1 seen in high-anxious individuals may be taken as a sign of increased sensory processing of the faces, most likely due to projections from the amygdala or other motivational centers to the visual cortex (Lang, Bradley, et al, 1998;Pourtois, Grandjean, Sander, and Vuilleumier, 2004).…”
Section: Discussionmentioning
confidence: 99%